Memaknai Kecenderungan Penyelesaian Konflik Batas Wilayah Ke Mahkamah Konstitusi - Soeroso, Fajar Laksono (Jurnal Konstitusi, 2012)
The trend of border conflict resolution to the Constitutional Court is interesting to analyzed. This analysis founded three interesting things that the Supreme Court decision did not resolve the problem but it raises a new problem, the precedent decision of the Constitutional Court may cancelling the Supreme Court decision, and the trial process in Constitutional Court felt more fair and openess. From its trend emerging of new legal loophole, which the parties became adressat Supreme Court decision not run a Supreme Court decision. This legal loophole seemed to justify    the unlawful acts because the Supreme Court decision has binding and should be implemented.This trend is not a question of rivalry between the Supreme Court    and Constitutional Court, but rather about how the judiciary presents a reliable judicial process and is believed by the justice seekers so that decisions can resolve the problem and  implemented.